Driving pressure-guided ventilation and postoperative pulmonary complications in thoracic surgery: a multicentre randomised clinical trial. (January 2023) - Park, MiHye; Yoon, Susie; Nam, Jae-Sik; Ahn, Hyun Joo; Kim, Heezoo; Kim, Hye Jin; Choi, Hoon; Kim, Hong Kwan; Blank, Randal S.; Yun, Sung-Cheol; Lee, Dong Kyu; Yang, Mikyung; et al.
Abstract: Background: Airway driving pressure, easily measured as plateau pressure minus PEEP, is a surrogate for alveolar stress and strain. However, the effect of its targeted reduction remains unclear. Methods: In this multicentre trial, patients undergoing lung resection surgery were randomised to either a driving pressure group ( n =650) receiving an alveolar recruitment/individualised PEEP to deliver the lowest driving pressure or to a conventional protective ventilation group ( n =650) with fixed PEEP of 5 cm H2 O. The primary outcome was a composite of pulmonary complications within 7 days postoperatively. Results: The modified intention-to-treat analysis included 1170 patients (mean [standard deviation, sd ]; age, 63 [10] yr; 47% female). The mean driving pressure was 7.1 cm H2 O in the driving pressure group vs 9.2 cm H2 O in the protective ventilation group (mean difference [95% confidence interval, CI]; −2.1 [−2.4 to −1.9] cm H2 O; P <0.001). The incidence of pulmonary complications was not different between the two groups: driving pressure group (233/576, 40.5%) vs protective ventilation group (254/594, 42.8%) (risk difference −2.3%; 95% CI,  −8.0% to 3.3%; P =0.42). Intraoperatively, lung compliance (mean [sd ], 42.7 [12.4] vs 33.5 [11.1] ml cm H2 O −1 ; P <0.001) and P a o 2 (median [inter-quartile range], 21.5 [14.5 to 30.4] vs 19.5 [13.5 to 29.1] kPa; P =0.03) were higher and the need for rescue ventilation was less frequent (6.8% vs 10.8%; P =0.02) in the driving pressure group. Conclusions: In lung resection surgery, a driving pressure-guided ventilation improved pulmonary mechanics intraoperatively, but did not reduce the incidence of postoperative pulmonary complications compared with a conventional protective ventilation. Clinical trial registration: NCT04260451.